Empowering Educators : Self-Efficacy and Psychological Safety in Driving Employee Engagement - Eapen, Sonia; Shamshuddin, Shaik; Mayur, Shruthi J. (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study aimed to capture how psychological safety (PS) and self-efficacy (SE) influenced employee engagement within the teaching profession. It further explored how these relationships varied across different demographic groups, focusing on teachers with children, varying levels of work experience, and gender differences. Design/Methodology/Approach : The study used a quantitative survey methodology. The survey participants included 200 teachers from a major Indian city. The results were analyzed using path analysis. The research examined the influence of SE, PS, and demographic factors (gender, parental status, and work experience) on the engagement level of teachers. Findings : The study revealed that PS consistently influenced employee engagement among teachers, while self-efficacy showed limited direct impact overall. Teachers without children experienced positive effects from both PS and SE, whereas those with children benefited primarily from PS. Across all experience levels—from 5 to over 15 years—both factors contributed positively to engagement, highlighting the value of a psychologically supportive environment. PS enhanced engagement for male teachers. However, SE did not show any significant effect. Research Implication : This study underscored the need for tailored engagement strategies, especially gender-specific ones, to enhance teacher engagement. Originality/Value : Educators shape India’s future human capital, driving the nation’s economic growth. Prioritizing the factors that enhance their performance is vital for sustaining progress and unlocking the full potential of our educational system.